2019
DOI: 10.3368/jhr.56.3.0118-9267r2
|View full text |Cite
|
Sign up to set email alerts
|

Disparities and Discrimination in Student Discipline by Race and Family Income

Abstract: Black and poor students are suspended from U.S. schools at higher rates than white and non-poor students. While the existence of these disparities has been clear, the causes of the disparities have not. We use a novel dataset to examine how and where discipline disparities arise. By comparing the punishments given to black and white (or poor and non-poor) students who fight one another, we address a selection challenge that has kept prior studies from identifying discrimination in student discipline. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 18 publications
6
80
0
Order By: Relevance
“…Dating back to the time when the U.S. Department of Education's Office of Civil Rights released its scathing report about school discipline practices, Black students comprised 18% of the nation's student population, but 48% of those students were suspended from school at least once indicating that Black students were much more likely to be suspended than would be expected (Civil Rights Data Collection, 2014). Essentially, being Black and from a low-socioeconomic household have been shown to be significant factors in predicting discipline outcomes, such as being suspended multiple times in the same year (Barrett et al, 2017). Even when policy-driven attempts to reduce suspension are successful overall, the disproportionate suspension persists (Jones, 2017;Trinidad, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dating back to the time when the U.S. Department of Education's Office of Civil Rights released its scathing report about school discipline practices, Black students comprised 18% of the nation's student population, but 48% of those students were suspended from school at least once indicating that Black students were much more likely to be suspended than would be expected (Civil Rights Data Collection, 2014). Essentially, being Black and from a low-socioeconomic household have been shown to be significant factors in predicting discipline outcomes, such as being suspended multiple times in the same year (Barrett et al, 2017). Even when policy-driven attempts to reduce suspension are successful overall, the disproportionate suspension persists (Jones, 2017;Trinidad, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, studies suggested that cross-school variation in discipline policies explain a substantial portion of the discipline gap (Anderson & Ritter, 2018). More recently, however, research using more extensive data and empirical approaches have found that discipline gaps persist both across and within-schools and districts (Barrett, McEachin, Mills, & Valant, 2019;Gopalan & Nelson, 2019;Owens & McLanahan, 2019). Again, it is important to exercise caution when interpreting results from these studies given the use of convenience samples of data in almost all of these studies.…”
Section: Racial/ethnic Discipline Gapsmentioning
confidence: 99%
“…Will they explain a larger variation in these discipline gap measures? Will discipline gap measures using alternative outcomes such as length of suspensions/expulsions be more informative (also, see Gopalan & Nelson, 2019;Barrett et al, 2019 who explore these measures using statewide data)? These are questions ripe for future explorations.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…School discipline is a balancing act. School administrators have to take into consideration many factors: trying to create a safe environment while maintaining a welcoming climate; treating students equitably and recognizing circumstances that influence behavior; and convincing students with behavior issues to correct their behavior while trying not to interrupt the learning taking place in the classroom (Barrett, McEachin, Mills, & Valant, 2017). Getting discipline right is a very important characteristic of a good school.…”
Section: Ensuring Safety and Learningmentioning
confidence: 99%
“…Getting discipline right is a very important characteristic of a good school. There are many instances where getting discipline wrong is a recipe for disaster (Barrett et al 2017 Morello, et al 2012). These policies are to describe the responsibilities of all students and the consequences when behavior violations occur.…”
Section: Ensuring Safety and Learningmentioning
confidence: 99%